Settlement of Non-Litigation Rape Crime Cases in the Perspective of Islamic Law - Atika, Atika; Andriyani, Andriyani; Putri, Adelia Salsabila (Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to study Islamic law resolving non-litigation rape cases in Beringin Makmur Dua Village, Rawas Ilir District, Musi Rawas Regency, South Sumatra Province. This research is based on the existence of rape cases resolved peacefully, even though the case should have been more appropriate if it had been resolved according to the law in force in Indonesia. This research is a field research or empirical research type. The approach method used is a qualitative approach. Data sources are primary and secondary, collected using interviews and documentation techniques. The analysis was carried out in a qualitative descriptive. This study concluded that resolving rape cases through non-litigation in Beringin Makmur Dua Village, Rawas Ilir District, was not following Islamic law. Even though Islamic law strongly recommends solving problems peacefully, not all cases, such as the hudud jarimah, can be resolved peacefully. One of the hudud jarimah is adultery or rape. According to Islamic law, the perpetrator of the rape must be subject to adultery sanctions, namely stoning or flogging. It is intended to provide a deterrent effect on perpetrators and society in general.